Developing low carbon economies: An aggregated composite index based on carbon emissions. (October 2019) - Mohsin, Muhammad; Rasheed, A.K.; Sun, Huaping; Zhang, Jijian; Iram, Robina; Iqbal, Nadeem; Abbas, Qaiser
Highlights: Aggregate Composite Index (ACI) has been developed. ACI contains meaningful, comprehensive and relevant set of indicators. DEA like composite indicator has been used to construct ACI. ACI considers energy, economic and environmental indicators. ACI shows the ranking of energy and environmental measures. Abstract: Energy indices provide a clear summary to measure the energy performance of the country which is a prerequisite for policy making. Increasing rate of greenhouse gases (GHGs) emissions are causing dangerous climate changes which seem irreversible. Therefore, it is vital to rank countries with the highest GHGs and carbon emissions in order to develop low carbon economies. This requires a comprehensive statistical analysis. In this study, we develop an aggregated composite index (ACI) of energy security and environmental sustainability for each of the world's highest GHGs and CO2 emitting countries. Our index is based on a comprehensive set of indicators including carbon emission and energy metrics. Composite indicator has been used to combine all the indicators in a holistic way. Higher values show a better efficiency and vice versa. The analysis reveals that there are considerable differences in performances of top and low ranked countries, Canada and Brazil respectively. We ranked the countries based on their efficiency score from top-down. Analysis also provides a roadmap and guidelines for the future policymakers.